Immunosurveillance and molecular detection of hepatitis B virus infection amongst vaccinated children in the West Gonja District in Savanna Region of Ghana. - Theophilus Quaye (Public Library of Science (PLoS), 2021)
Hepatitis B vaccination is the most effective preventive measure in reducing the incidence of chronic hepatitis B virus (HBV) infection and its consequences such as cirrhosis, hepatocellular carcinoma, liver failure and death. Ghana introduced the universal HBV vaccination in the national Expanded Programme on Immunization in 2002. The current study sought to determine the sero-protection rate and the prevalence of HBV infection among fully vaccinated children in the West Gonja District in the Savanna Region of Ghana. This cross-sectional study recruited three hundred and fifty (350) fully vaccinated children who visited West Gonja Catholic Hospital from September to December 2019 for healthcare. Structured questionnaires were administered to obtain information on the demographics. The clinical history of the participants was obtained from the hospital records. Sera were separated from 2-5ml of blood sample collected from each participant after informed consent had been sought from their parents/guardians. Sera were tested for HBsAg, anti-HBs and anti-HBc using ELISA. Samples positive for HBsAg or anti-HBc were tested for HBV DNA by Real-Time Polymerase Chain Reaction. The overall sero-protection rate (anti-HBs titers ≥ 10 mIU/mL) among the studied participants was 56% with anti-HBs geometric mean titer (GMT) of 95.7 mIU/mL (± 6.0; 95% CI) compared with GMT of 2.8 mIU/mL (± 0.2; 95% CI) among non-seroprotected participants. There was no statistically significant difference in sero-protection rate between males and females (p-value = 0.93) and in relation to age (p-value = 0.20). The prevalence of HBV infection among studied participants as determined by the HBV DNA/HBsAg positivity was 1.4% while anti-HBc sero-positivity was 2%. Even though the sero-protection rate and HBV infection rate reported in the current study compares with that of other international studies further studies need to be conducted to understand the factors related to sero-protection and HBV infection rate in the Savanna Region of Ghana.